Methods of drying leaf samples of barbados cherry sugar cane and citrus for determination of dry matter and macronutrients contents - Rocha, Lucian Cima de Melo; Prado, Renato Mello; Dias, José Luiz Carvalho de Souza; Vieira, Douglas Silva Tobias (Comunicata Scientiae, 2011)
The drying of leaf samples with use of a microwave oven can be a viable alternative for obtaining rapid results of leaf analysis. The objective of this paper was to compare the drying process in FMO and greenhouse forced air ventilation in the determination of dry matter and macronutrient leaf crops of citrus, sugar cane and barbados cherry. The treatments consisted of two drying methods, an air forced circulation greenhouse regulated to a temperature of 70 0C and FMO, in which each sample was subjected to drying in 3 cycles of 5 minutes, 1 cycle of 3 minutes, 1 cycle 2 minutes and 1 cycle of 1 minute, reaching constant weight. The experiment was a hierarchical arrangement 2 x 3 (two drying methods and three species), with six replicates. Using the method of FMO drying and the air forced circulation greenhouse did not influence the dry weight and macronutrient content of leaves of the crops of citrus, barbados cherry and sugar cane, indicating that the use of FMO is a viable alternative to be used in laboratories of foliar analysis.